Exploring parental country of birth differences in the use of psychostimulant medications for ADHD: a whole‐population linked data study. (12th October 2014) - Ghosh, Manonita; Holman, C. D'Arcy J.; Preen, David B.
Abstract Objective: To explore parental country of birth differences in the use of stimulants for attention deficit hyperactivity disorder (ADHD) in Western Australian (WA) children and adolescents. Methods: Statutory WA stimulant notification and dispensing records from 2003 to 2007 were linked to whole‐population state data from 1980 to 2007. Parental attributes were obtained through the WA Family Connections genealogical linkage system. Using multivariate logistic and linear regression, the differences in WA stimulant use for ADHD by parental country of birth, socioeconomic status and geographical remoteness were examined. Results: Of 671, 231 people born in WA between 1980 and 2007, 13, 555 (2%) used stimulants for ADHD. Of these, 734 (5%) had parents born in Africa, Asia, the Middle East or South America, and 12, 006 (87%) had parents born in Australia, North America and Europe. Children and adolescents with parents born in traditionally non‐Anglophonic countries were less likely to be treated with stimulants (OR=0.17, 95%CI 0.14–0.21) than those with parents born in Anglophonic countries. Socioeconomic advantage and residential remoteness were also significant independent predictors of a decreased likelihood of stimulant use. Conclusions: The results highlight the importance of improving knowledge about cultural differences in access to and attitudes towards the diagnosis of ADHD and different approaches to its treatment.